The modified early age strains development model for the case of two-way restraint conditions - Sannikava Volha; Tur Viktar (MATEC Web of Conferences, 2021)
This paper proposes a design model (2D MSDM) for assessment the early-age stress-strain parameters of two-axially restrained expansive concrete elements. The analytical model allows defining the restrained expansion strains and corresponding self-stresses in case of arbitrary restraint conditions in orthogonal directions by taking into consideration the elastic-plastic behavior of concrete during the expansion period. The results of solution according to the proposed model were compared with the experimental results of expansive concrete elements with orthogonal confinement carried out by authors and other researchers.